Water quality and primary productivity at cage culture and non cage culture sites at Batang Ai HEP resevoir, Lubok Antu, Sarawak - Koh, Karen (Universiti Malaysia Sarawak (UNIMAS), 2016)
Cage culture activities at Batang Ai Reservoir have expanded significantly over the past few years. However, the water quality and primary productivity at the reservoir has not been well documented despite its importance for aquaculture expansion. Therefore, the objective of this study carried out in August 2015 and February 2016 was to determine the water quality and primary productivity at three stations in the reservoir. Station A and station C were cage culture sites whereas station B was a non-cage culture site. Results showed thermocline level at 9 to 15 m depth and temperature at 0.2 m of station C was the highest. Dissolved oxygen (DO) decreased with increasing depth and DO at 0.2 m for all stations (5.76 to 7.37 mg/L) was suitable for fish survival. The pH ranged from 6.11 to 6.74. Conductivity was significantly higher at 20 m depth (33 to 55 μS/cm) for all stations whereas turbidity was higher at 10 m depth (2.23 to 4.50 NTU). Chlorophyll-a values ranged from 0.34 to 59.63 pg/L and were mostly highest at station B. BODs values ranged from 2.18 to 4.75 mg/L. Highest TSS values were recorded at 30 m depth at all stations (2.333 to 9.533 mg/L). Ammonia values ranged from 0.01 to 0.94 mg/L. Elevated nitrate and nitrite values were recorded at 10 m depth of station A in February. Silica was highest at station A (August) and at station C (February) while orthophosphate was highest at station A except for at 0.2 m. The 24-hour profiling at station C showed slight fluctuation of temperature at 10 m depth. Turbidity at 10 m depth was the highest and a sudden drop in turbidity occurred at 1.00 PM. DO at sub-surface fluctuated with a drastic drop at 10.00 PM and conductivity was highest at 30 m depth with little fluctuations. The pH profiles showed slight increase at every depth throughout the 24 hour period. Overall NPP was the highest at station A during both trips. This study showed higher amount of nutrients and NPP at cage culture sites. Therefore, aquaculture activities may have impacted on the water quality and primary productivity of Batang Ai Reservoir but the impacts are limited to the area around the cage cultures